Pengaruh Disiplin Kerja terhadap Kinerja Karyawan pada UPT Depo Kereta PT. Kereta Api Indonesia (Persero) Daerah Operasi 3 Cirebon - Tubagus Arif Abimanyu; Aminuddin Irfani (UNISBA Press, 2023)
Abstract. Human resources are one of the factors in an institution that must be considered and not ignored.Employee Performance Assessment plays an important role in the extent to which the success of an organization has been achieved. However, not all of these things go according to the company's expectations, because not all employees have the same skills and enthusiasm for work. One of the factors that affect human resources is the discipline factor. In this study aims to determine the effect of work discipline on employee performance at The Effect of Work Discipline on Employee Performance The Effect of Work Discipline on Employee Performance at UPT Depo Kereta PT. Kereta Api Indonesia (Persero) Operational Area 3 Cirebon. The method used is a quantitative method with a descriptive analysis approach and verification analysis. The population in this study were 79 people. The sampling method uses a saturated sample or 79 people in the company are used entirely. The analysis technique used is a simple regression analysis technique. Based on the results of the study stated that there is a relationship with a